Contemporary novelists and the aesthetics of twenty-first century American life - Kingston-Reese, Alexandra, 1989- (New American canon., 2019)
"Contemporary culture is full of anxiety. But what happens when art, which usually purports to soothe us, actually disturbs us? What affective distortions do aesthetic experiences afford us when solace isn't the ultimate ambition? What happens when art fails, or when we fail to engage with art? When aesthetic experience negates the profound, verges on the automatic, and is troubled by dissonant feelings? Contemporary Novelists and the Aesthetics of Twenty-First Century American Life explores how the contemporary novel is increasingly shifting the way we think about art's effects on us to illuminate how novelistic mediations of and meditations on aesthetic experience are enriched by a paradoxical concern with the ineffability and inexpressibility of personal and communal losses or disasters. Reading alongside key practitioners in contemporary fiction and art criticism, including Teju Cole, Jennifer Egan, Sheila Heti, Siri Hustvedt, Chris Kraus, Ben Lerner, and Zadie Smith, Alexandra Kingston-Reese suggests a rip away from contentment, comfort, and habit through five modes of against--as slant rhymes, afterimage, transcription, synaesthesia, and suspension--which capture not only affective dissonance, but formal experimentation"--